Efficacy and safety of micro-implant anchorage in Angle class II malocclusion orthodontic treatment: A protocol for systematic review and meta-analysis. Issue 50 (11th December 2020) - Wang, Kaiting; Fan, Hongliang; Yang, Hongmei; Li, Jianbin; Xie, Weihong
Abstract: Background: Angle class II malocclusion is clinically complex and common malocclusion type, which affects beauty. Conventional treatment has the disadvantages of long course of treatment, high cost, easy recurrence and limited curative effect. Clinical practice shows that micro-implant anchorage has certain advantages in the treatment of Angle II malocclusion, but lacks the evidence of evidence-based medicine. This study systematically evaluates the efficacy and safety of micro-implant anchorage in the treatment of Angle class II malocclusion. Methods: A systematic search was performed by retrieving on English databases (PubMed, Embase, Web of Science, and the Cochrane Library) and Chinese databases (CNKI, Wanfang, Weipu [VIP], CBM). Besides, manually search for Google and Baidu academic of micro-implant anchorage in the treatment of Angle class II malocclusion in randomized controlled clinical research. The retrieval time limit was from the establishment of the database to September 2020. Two researchers independently extracted and evaluated the quality of the data in the included study. A meta-analysis was performed using RevMan5.3 software. Results: In this study, the efficacy and safety of micro-implant anchorage against Angle class II malocclusion were evaluated by SNA, BNA, ANB, NLA°, Adverse reaction. Conclusions: This study will provide reliable evidence-based evidence for the clinical application of micro-implant anchorage in the treatment of Angle class II malocclusion. Ethics and dissemination: Private information from individuals will not be published. This systematic review also does not involve endangering participant rights. Ethical approval was not required. The results may be published in a peer-reviewed journal or disseminated at relevant conferences. OSF Registration number: DOI 10.17605/OSF.IO/UPBR8.